Features of providing specialized medical care to adult patients with neoplasms of the parotid salivary glands - V. A. Belchenko; I. V. Chantyr (Здоровье мегаполиса, 2022)
Introduction. For many years, the issues of diagnosis, planning and surgical treatment of adult patients with neoplasms of the parotid salivary glands (PSG) have remained relevant.Objective: to identify the features of the specialized medical care provided to adult patients with PSG neoplasms.Materials and methods. We analyzed the statistical data of specialized medical care provided to patients with PSG neoplasms in institutions of the Department of Health of the city of Moscow. To characterize the patients, a sample of medical documentation of 302 patients who were on inpatient treatment at the Maxillofacial Hospital for War Veterans was conducted for the period from January 2017 to April 2022.Results and discussion. The study group included 116 men (38.41 %) and 186 women (61.59 %), aged 19 to 81 years (mean age 52.27 ± 0.23 years). All patients underwent surgical intervention on the PSG with the dissection and preservation of peripheral branches of the facial nerve. As a result, the study group of patients was divided into 3 subgroups: the 1st – with benign neoplasms (n = 258), the 2nd – with malignant neoplasms (n = 24), the 3rd – with tumor-like lesions (n = 20). Some features of diagnostics and planning are revealed, algorithm of surgical treatment are discussed.Conclusions. Despite the significant development of both diagnostic methods and surgical intervention techniques, there is a need to improve clinical recommendations and treatment protocols with a clearer indication of criteria in choosing surgical treatment. Medical care for adult patients with PSG neoplasms should be carried out on the basis of specialized centers, which will minimize the number of diagnostic errors and postoperative complications.